Resistance pattern of breakthrough urinary tract infections in children on antibiotic prophylaxis - Ali Reza Nateghian; Joan L. Robinson; Shahab Mohandessi; Nakysa Hooman (Journal of Infection and Public Health, 2009)
Summary: Prophylactic antibiotics are commonly used for prevention of urinary tract infections (UTIs) in children. It was postulated that the organisms and resistance patterns of breakthrough infections would differ with the choice of antimicrobial prophylaxis. This was a retrospective descriptive study of all breakthroughs UTI from 2000 to 2006 in children over 1 month of age discharged from a referral children's hospital in Tehran, Iran on continuous antibiotic prophylaxis for UTIs. Fifty-seven children discharged on prophylaxis had breakthrough UTIs of which 32 (56%) had a previously diagnosed urinary tract anomaly. Escherichia coli was responsible for the majority of infections irrespective of choice of prophylaxis. Thirty-three of 56 breakthrough UTIs (59%) were with organisms that were resistant to the prophylactic antibiotic. There was an increased incidence of resistance to prophylaxis in children on cefixime (16 of 22; 78%) when compared with children on cephalexin (7 of 19; 37%; p = 0.02) and a trend toward increased resistance when compared with children on trimethoprim–sulfamethoxasole (3 of 8; 37%) (p = 0.10). In conclusion, the resistance pattern of organisms causing breakthrough UTIs varies with the choice of prophylaxis which should be taken into consideration in chosing empiric therapy for such infections. Keywords: Antibiotic prophylaxis, Cefixime, Pyelonephritis, Resistance, Antibiotic, Urinary tract infection